Planning and design of appropriate irrigation systems for KCAET farm - JAYAN, P. R; Sudheer Babu, P; Usha, V; Varghese Philip (Tavanur Kelappaji College of Agricultural Engineering and Technology, 1990)
project report
project report
Keywords: project report